Significance of tissue microbiopsies in fine needle aspiration cytology - Jaswanthini, A. R.; Prathap, D. Vishnu; Swaminathan, K. (International Journal of Research in Medical Sciences, 2018)
Background: Fine Needle Aspiration Cytology smears prepared through conventional method, often contain well preserved viable tissue fragments which are intact (Tissue Micro biopsies). They will provide information on the tissue architecture and contribute to the tumour ontogeny. Methods: A prospective study of significance of tissue micro biopsies in FNAC were studied and interpreted in the Cytopathology laboratory of Department of Pathology, Tirunelveli Medical College, Tirunelveli. 100 cases with clinically palpable Swellings were studied. Results: Out of 100 cases, 82% of cases were coming under the category of conventional FNAC, 10% of the cases were USG guided and 8% were falling under CT guided FNAC. The organs with highest yield of micro biopsies were lymph nodes 34 cases (34%) followed by breast 24 cases, thyroid 11 cases, lung 8 cases, salivary gland 7 cases, liver and bone and soft tissue 4 cases each, abdominal mass 3cases, pancreas 2 cases, and single case each of ovary, spleen, anterior mediastinum. Of the total 100 cases, 56% of the cases were malignant and 44% of the cases were benign. Among the 56 malignant tumours 41(73.2%) cases were primary tumours and 15cases (26.8%) were metastatic tumours. Conclusions: FNA smears containing micro biopsies help in diagnosis, typing of tumour and predicting possible primary sites in cases of metastatic tumours which were not possible by cytology alone. Hence, this technique can be used to increase the diagnostic accuracy of FNAC if put into practice.